Determining the Amount of Histamine Levels in Canned Tuna Fish Marketed in Supermarkets of Tabriz City - Javad Mohtadi nia; Mehrnoush Zakerzadeh; Mehdi Goudarzi; Hossein Rahman pour; Hossein Khadem Haghighian (Fasa University of Medical Sciences, 2014)
Background & Objective: Histamine poisoning which is induced from seafood is the most common disease around the world. Determining the amount of histamine in canned tuna fish shows not only the healthy quality of fish, but also it is effective in protecting the health and safety of the consumers. Materials & Methods: In this cross-sectional study, 60 samples of histamine content canned tuna fish marketed in supermarkets of Tabriz city was analyzed through ELISA method. Histamine levels in the samples were compared based on the time between the production and the production seasonwith limited range. Statistical analysis was performed using SPSS software version 16. Results: Histamine levels between 5-200.3 mg/kg were different. Histamine levelin canned food was 30 % lower and 70% higher than the permissible limit (50 mg kg) in some cans. Histamine levels in canned tuna produced in North and South regions were statistically significant (p<0.05).Canned tuna fish produced in summer and autumn, respectively, had the highest and lowest levels of histamine. Conclusion: According to high percentage of canned tuna, which have histamine more than permissible limit, the risk of histamine toxicity is there for consumers of such kind of food.